Low-Cost, Practical Data Confidentiality Support for IoT Data Sources - Tenório, Viviane; Souza, Leonardo; Albuquerque, Maxwell; Marinho, Rodolfo; Silva, Matteus; Brito, Andrey (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
IoT is one of the most discussed topics in distributed systems currently, having new applications and interesting solutions developed every day. Nevertheless, to make applications possible and widespread, the costs of data acquisition and transmission must be overcome. Raspberry Pi 3, in this sense, has become a good cost-effective solution for many IoT application. In this paper, we present a low-cost, secure Smart Meter built on Raspberry Pi 3. This solution is divided in three stages: secure data acquisition, data ciphering and secure data transfer. The main contribution consists on the level of data protection which goes beyond the regular authentication and secure communication protocols. Through this approach, sensitive data can be kept secure even if the cloud provider is untrusted. This is a flexible, simple, efficient, and low-cost solution that can be applied in many other IoT application contexts.